Baicalin Regulates Neuronal Fate Decision in Neural Stem/Progenitor Cells and Stimulates Hippocampal Neurogenesis in Adult Rats - Zhuang, Peng‐Wei (CNS Neurosci Ther, 2013)
BACKGROUND: Recent studies revealed that baicalin, a flavonoid compound derived from the root of Scutellaria baicalensis Georgi, could promote neuron differentiation of NSPCs after commencing the differentiation process in vitro. However, this may not be the most efficacious strategy to determinate cell fate. Here, we have investigated whether baicalin can influence early events of neuron generation and stimulate adult neurogenesis. RESULTS: Transient exposure of NSPCs to baicalin during proliferation could activate Mash1 to alter the differential fate and increase the proportion of cells expressing neuronal markers. Seven days after, rats were exposed to transient cerebral ischemia, they were treated for 3 weeks with baicalin, BrdU labeling study showed that exposure to baicalin increased the number of newly generated cells in hippocampus, BrdU/NeuN double staining analysis indicated that baicalin could promote new neuron production after cerebral ischemia. Additionally, Morris water maze test showed that delayed postischemic treatment with baicalin improved cognitive impairment. CONCLUSIONS: These results identify the existence of a single molecule, baicalin, which can specify the neuronal fate of multipotent NSPCs and stimulate neurogenesis, making it a promising candidate for developing clinically relevant strategies to manipulate neuronal fate of NSPCs for brain repair.